SAT0482 Subclinical enthesopathy in psoriatic patients and its relation to other disease parameters: an ultrasound study. (15th June 2017) - Gouda, W; Ismail, M; Doma, M
Abstract : Background: Psoriasis is a chronic immune-mediated inflammatory skin disease characterized by reddish, thick patches covered with marked silvery scaling [1]. In about 70% of the patients, psoriasis is present many years before the onset of psoriatic arthritis [2]. The early recognition and therapeutic intervention especially with the new biologic treatments is critical to prevent the destructive and debilitating changes of psoriatic arthritis [3]. Enthesitis is inflammation at the attachment of tendons and ligaments to the bones, has been suggested as being the unifying feature of psoriatic arthritis, and the disease can be considered an enthesis associated disorder rather than primary synovitic arthropathy [4]. Objectives: We aimed to correlate the subclinical enthestitis in patients with psoriasis detected by means of power Doppler (PD) ultrasonography (US) with other disease parameters. Methods: 50 persons with a definite diagnosis of psoriasis with no clinical evidence of arthritis or enthesitis were selected. All patients underwent complete clinical assessment included Psoriasis severity (PASI) score, body mass index (BMI), PDUS evaluation of Achilles, quadriceps, patellar entheses and plantar aponeurosis. US findings were scored according to the Glasgow Ultrasound Enthesitis Scoring System (GUESS). Results: In 18 of 50 of patients (36%) PDUS found signs indicative of enthesopathy. The Achilles enthesis had the highest number of PDUS signs of enthesopathy (33.3%), followed by distal patellar enthesis (22.2%), proximal patellar enthesis (16.7%), quadriceps enthesis (16.7%), and plantar aponeurosis enthesis (11.1%) with variable enthesial morphostructural abnormalities. The GUESS score was directly correlated with age (p=0.012), disease duration (p=0.044), PASI (p=0.035), BMI (p=0.011), hyperuricemia (p=0.011). Conclusions: In addition to the importance of PDUS as a complimentery tool in examination of entheses in psoriatic patients, the presence of high PASI score together with the increased BMI and hyperuricemia in addition to long disease duration could be considered as predictive parameters for the presence of psoriatic enthesitis. References: Menter A, Gottlieb A, Feldman SR, et al. Guidelines of care for the management of psoriasis and psoriatic arthritis, section 1. Overview of psoriasis and guide lines of care for the treatment of psoriasis with biologics. J Am Acad Dermatol. 2008; 58(5):826–50. Dimitrios TB, Ioannis OT. Psoriatic arthritis. In: Klippel JH, ed.Primer on the Rheumatic Diseases. Atlanta, GA: Arthritis Foundation, 1997: 175–179. Rozenblit M, Lebwohl M. New biologics for psoriasis and psoriatic arthritis. Dermatol Ther. 2009; 22(1):56–60. McGonagle D, Conaghan PG, Emery P. Psoriatic arthritis: a unified concept twenty years on. Arthritis Rheum. 1999; 42:1080–7. Disclosure of Interest: None declared